Structural and Functional Basis for an EBNA1 Hexameric Ring in Epstein-Barr Virus Episome Maintenance - Deakyne, Julianna S.; Malecka, Kimberly A.; Messick, Troy E.; Lieberman, Paul M. (Journal of virology, 2017)
Epstein-Barr virus (EBV) establishes a stable latent infection that can persist for the life of the host. EBNA1 is required for the replication, maintenance, and segregation of the latent episome, but the structural features of EBNA1 that confer each of these functions are not completely understood. Here, we have solved the X-ray crystal structure of an EBNA1 DNA-binding domain (DBD) and discovered a novel hexameric ring oligomeric form. The oligomeric interface pivoted around residue T585 as a joint that links and stabilizes higher-order EBNA1 complexes. Substitution mutations around the interface destabilized higher-order complex formation and altered the cooperative DNA-binding properties of EBNA1. Mutations had both positive and negative effects on EBNA1-dependent DNA replication and episome maintenance with OriP. We found that one naturally occurring polymorphism in the oligomer interface (T585P) had greater cooperative DNA binding in vitro , minor defects in DNA replication, and pronounced defects in episome maintenance. The T585P mutant was compromised for binding to OriP in vivo as well as for assembling the origin recognition complex subunit 2 (ORC2) and trimethylated histone 3 lysine 4 (H3K4me3) at OriP. The T585P mutant was also compromised for forming stable subnuclear foci in living cells. These findings reveal a novel oligomeric structure of EBNA1 with an interface subject to naturally occurring polymorphisms that modulate EBNA1 functional properties. We propose that EBNA1 dimers can assemble into higher-order oligomeric structures important for diverse functions of EBNA1. IMPORTANCE Epstein-Barr virus is a human gammaherpesvirus that is causally associated with various cancers. Carcinogenic properties are linked to the ability of the virus to persist in the latent form for the lifetime of the host. EBNA1 is a sequence-specific DNA-binding protein that is consistently expressed in EBV tumors and is the only viral protein required to maintain the viral episome during latency. The structural and biochemical mechanisms by which EBNA1 allows the long-term persistence of the EBV genome are currently unclear. Here, we have solved the crystal structure of an EBNA1 hexameric ring and characterized key residues in the interface required for higher-order complex formation and long-term plasmid maintenance.